PERBAIKAN KUALITAS AIR BAKU PERUSAHAAN AIR MINUM (PAM) DENGAN BIOFILTRASI - Rudi Nugroho; Nusa Idaman Said (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2011)
A study to improve the raw water quality at Taman Kota Drinking Water Company was conducted by using pilot plant of biofiltration system. The pilot plant was run by pumpingthe raw water from river to the reactor continuously with various Hydraulic Retention Time. Samples of raw water and treated water were taken daily and analyzed for pH,Total Suspended Solid (TSS), Organic matter, Ammonia nitrogen and Detergent (MBAS). The results showed that performance of biofiltration system decreaed due to shortening Hydraulic Retention Times (HRT). The longer HRT caused bigger volume of biofiltration tank. Therefore, this study suggests that the optimum Hydraulics retention time is 1 hr. In this HRT, the treated water quality were 7.2 for pH, 40 mg/l for TSS, 10,7 mg/l for organic matter, 0.35 mg/l for ammonia nitrogen and 0.1 mg/l for MBAS. These resultscomply with the Regulation No. 582 year 1995 for raw drinking water quality (class B).